2017
DOI: 10.1038/s41467-017-00178-3
|View full text |Cite
|
Sign up to set email alerts
|

Every-other-day feeding extends lifespan but fails to delay many symptoms of aging in mice

Abstract: Dietary restriction regimes extend lifespan in various animal models. Here we show that longevity in male C57BL/6J mice subjected to every-other-day feeding is associated with a delayed onset of neoplastic disease that naturally limits lifespan in these animals. We compare more than 200 phenotypes in over 20 tissues in aged animals fed with a lifelong every-other-day feeding or ad libitum access to food diet to determine whether molecular, cellular, physiological and histopathological aging features develop mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
108
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(132 citation statements)
references
References 67 publications
21
108
1
1
Order By: Relevance
“…The modest, but significant extension of longevity in MF animals, associated with delayed onset of fatty liver disease and hepatocellular carcinoma, re-opens the issue of the relative importance of reduced caloric intake per se in the beneficial effects of CR as opposed to periods of fasting that occur as a result of lower food intake (Acosta-Rodriguez et al, 2017; Masoro, 2004). This work extends previous important findings from our laboratory (Anson et al, 2003) and others (Chaix et al, 2014; Xie et al, 2017). Because most humans already have about a 8 to 12h night fast built into their day, a longer daily fasting period may be required to confer health and survival benefits.…”
Section: Figuresupporting
confidence: 92%
“…The modest, but significant extension of longevity in MF animals, associated with delayed onset of fatty liver disease and hepatocellular carcinoma, re-opens the issue of the relative importance of reduced caloric intake per se in the beneficial effects of CR as opposed to periods of fasting that occur as a result of lower food intake (Acosta-Rodriguez et al, 2017; Masoro, 2004). This work extends previous important findings from our laboratory (Anson et al, 2003) and others (Chaix et al, 2014; Xie et al, 2017). Because most humans already have about a 8 to 12h night fast built into their day, a longer daily fasting period may be required to confer health and survival benefits.…”
Section: Figuresupporting
confidence: 92%
“…Studies in the previous century on rodents already demonstrated that inducing intermittent fasting, by feeding animals every other day or by other means, extends life span in a similar manner to caloric restriction [reviewed in (47)]. Two recent studies in mice suggest the same, although the effects are not as large as full caloric restriction (48), and outcomes for systemic ageing have been questioned (49). Human data on intermittent fasting are promising (46) and have on July 4, 2020 http://advances.sciencemag.org/ Downloaded from potential application in specific diseases (50), but conclusive evidence from clinical trials is currently lacking (51).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as described in the previous section, we observed weight loss in mice with diet-induced obesity subjected to intermittent fasting with preservation of β-cell mass despite continued high fat feeding and restoration of β-cell function (119). In another study of chronic intermittent fasting in both young and aged mice, an every other day fasting regimen prolonged lifespan, reduced left ventricular mass and attenuated ageing-induced cardiac hypertrophy, and improved glucose tolerance (240), but did not affect other metabolic parameters in young mice, pointing to an important interaction between age at which the intermittent fasting regimen was initiated and metabolic outcomes. An important note of caution is the observation for increased insulin resistance with every other day fasting regimens in young obese mice in our studies (119), which was mirrored by a trend towards increased circulating insulin levels in young mice (240) as well as evidence for increased hepatic insulin resistance in rats (157).…”
Section: Benefits Of Intermittent Fasting In Animal Models On Cardiommentioning
confidence: 99%
“…In another study of chronic intermittent fasting in both young and aged mice, an every other day fasting regimen prolonged lifespan, reduced left ventricular mass and attenuated ageing-induced cardiac hypertrophy, and improved glucose tolerance (240), but did not affect other metabolic parameters in young mice, pointing to an important interaction between age at which the intermittent fasting regimen was initiated and metabolic outcomes. An important note of caution is the observation for increased insulin resistance with every other day fasting regimens in young obese mice in our studies (119), which was mirrored by a trend towards increased circulating insulin levels in young mice (240) as well as evidence for increased hepatic insulin resistance in rats (157). These findings suggest that the duration of fasting may be a stress, and will need to be carefully titrated depending upon the species (as 24 hours of fasting in a mouse is perhaps equivalent to a much longer period of fast in humans given differences in lifespan).…”
Section: Benefits Of Intermittent Fasting In Animal Models On Cardiommentioning
confidence: 99%
See 1 more Smart Citation